Sosialisasi Pengelolaan Aset dan Perawatan Peralatan Pengrajin Tembaga Merapi Karya Cipta di Tumang, Cepogo, Boyolali - Nabyla Aulya; Melati Sahlita; Jesica Ega Ramadani; Ferulina Keysha Azzahra; Hari Purwanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Asset management and equipment maintenance are crucial aspects in supporting smooth business operations, particularly in the copper crafts industry. Merapi Karya Cipta, located in Dusun III, Tumang, Cepogo District, Boyolali Regency, owns various production equipment assets that play a direct role in the work process, yet their management remains rudimentary and unplanned. This community service activity aims to increase copper craftsmen's understanding and awareness of the importance of asset management and equipment maintenance to improve operational efficiency. Qualitative methods were used through observation, interviews, and direct outreach to the craftsmen. The results of the activity demonstrated increased knowledge and a shift in participants' perspectives on business management, particularly regarding equipment maintenance and division of labor. The craftsmen began to understand that routine maintenance can be performed simply and does not always require significant costs. Therefore, this activity is expected to help maintain the continuity of the production process, reduce the risk of equipment damage, and support increased productivity and the well-being of the local community.